Analisis Pengembangan Potensi SDM dan Kendala Yang Dihadapi Produksi Rumput Laut di Kabupaten Sumenep - Vivin Anindya Lisna; Zainiyatul Afifah; Mudji Kuswinarno (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This research aims to analyze the development of human resource (HR) potential and the obstacles faced in seaweed production in Sumenep Regency. Sumenep Regency has great potential in the seaweed sector, but the development of this sector is faced with various challenges that hinder the optimization of production results. This research methodology uses a qualitative approach with data collection techniques through in-depth interviews, field observations and documentation studies. The main focus of the research is to evaluate the capacity of human resources involved in seaweed production, as well as identifying obstacles that hinder the development of this sector. It is hoped that this research will provide useful insights for formulating better HR development strategies and overcoming production constraints. The recommendations resulting from this study will become the basis for policies and intervention programs aimed at increasing the effectiveness of seaweed production in Sumenep Regency, as well as encouraging sustainable growth of this sector. The conclusion, from the analysis of potential human resource development and obstacles faced by Sumenep seaweed production, shows that although there are major obstacles such as limited capital, access to training, extreme weather, and lack of technical marketing knowledge, they can hinder the achievement of production targets. Keywords: Human Resource Development